Pressure leaching characteristics of a magnetically enhanced concentrate with specific refrence to the precious metal components - Craig, Deborah Carol (My University, 2008)
ABSTRACT The overall metallurgical processing of precious group metals (PGM) contained in mined ores involves a number of hydrometallurgical operations for the removal of base metals and sulphidic sulphur before the final refining of individual PGM’s to saleable metal. The final process in this sequence is a batch pressure leach in which further base metals are removed prior to the introduction into the Precious Metals Refinery (PMR). Significant amounts of PGM losses are however experienced in this stage, which is called the tertiary leach. This is attributed to difficulties in monitoring and controlling the leach within a tight range of parameters. The losses are highly undesirable, as the precious metal rich stream then requires additional process steps to recover the values, which negatively impacts on the pipeline time. This investigation will focus of the tertiary leach. The exact reasons, chemical mechanisms and driving force which influence the dissolution of precious metals is not fully known and understood. However, since the plant often experiences significant PGM dissolution, it is critical to understand and establish a knowledge base to provide a more scientific methodology for improving the control of this process. The objectives of this study are defined as : 1. The identification of conditions under which significant PGM dissolution is observed. 2. Establishing the order in which the precious metals solubilise. 3. Determining the cause of PGM solubilisation. 4. Illustrating the parameters required to monitor and control the end point to consistently maximise base metal removal and minimise PGM losses to leach liquors. It is experimentally observed that the most affected PGMs during the tertiary leach are rhodium, ruthenium and palladium. All are observed in different amounts in the leach liquors when the reduction-oxidation potentials exceed 600 mV. The most important finding of this study is that the soluble PGMs originate from a phase that is termed Pd type 1 mineral which is a fine grained phase that is already present in the leaching circuit in the feed material presented to the tertiary pressureleach. This phase appears to be produced in the primary pressure leach. It is postulated that it arises due to the presence of base metal sulphides that are entrained with the magnetic fraction of the material. During the primary pressure leach, these base metal sulphides appear to form fine grained material that result in the formation of the Pd type 1 phase seen in the tertiary leach. If the amount of entrained base metal sulphides in the magnetically enhanced concentrate (MEC) is reduced or removed completely, it will remove the source of the soluble PGMs and consequently PGM losses to the leach liquor will only occur in the event of severe and extreme over-leaching. The first prize for controlling the end point of this leach is to consistently maximise base metal leaching while minimising PGM losses. The end point of the leaching process is currently determined by monitoring the redox potentials of the slurry samples taken at various intervals. A problem with this approach is that the redox determined under atmospheric pressure conditions differs from the values in the pressure vessel. Another drawback is that in the redox range of 550 mV to 650 mV, the potentials are extremely sensitive and huge increases are experienced over small time intervals. This makes it very difficult to predict the exact end point consistently for different batches. A better approach would be to identify alternative parameters that would allow ample time to make an informed decision regarding the end point. This appears to be possible by monitoring the copper and nickel in solution. When the concentration of these two base metals increases substantially, this would signal the start of the termination sequence and cooling down of the reactor. The increase for copper appears to be from ~19-39 g/l and nickel from ~6.5-8.5 g/l for the ore tested in this study.